2005
DOI: 10.1002/ana.20548
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea enhances SMN2 gene expression in spinal muscular atrophy cells

Abstract: Spinal muscular atrophy (SMA) is a motor neuron disease caused by dysfunction of the survival motor neuron (SMN) gene. Human SMN gene is present in duplicated copies: SMN1 and SMN2. More than 95% of patients with SMA lack a functional SMN1 but retain at least one copy of SMN2. Unlike SMN1, SMN2 is primarily transcribed into truncated messenger RNA and produces low levels of SMN protein. We tested a therapeutic strategy by treating cultured lymphocytes from patients with SMA with hydroxyurea to modify SMN2 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 49 publications
1
62
1
1
Order By: Relevance
“…Previous reports have also shown a lack of correlation of FL/D7 ratios in blood cells, 20,28,32 fibroblasts 16 and lymphoblasts. 18 In the four haploidentical sisters, we found no differences in the FL/D7 ratios, either in fibroblasts or in lymphoblasts. In fibroblasts from eight discordant families, Helmken et al 33 found no differences in FL/D7 ratios between affected and unaffected siblings, although they did find ratio differences in lymphoblasts in one family.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Previous reports have also shown a lack of correlation of FL/D7 ratios in blood cells, 20,28,32 fibroblasts 16 and lymphoblasts. 18 In the four haploidentical sisters, we found no differences in the FL/D7 ratios, either in fibroblasts or in lymphoblasts. In fibroblasts from eight discordant families, Helmken et al 33 found no differences in FL/D7 ratios between affected and unaffected siblings, although they did find ratio differences in lymphoblasts in one family.…”
Section: Discussionmentioning
confidence: 59%
“…In vitro experiments with phenylbutyrate (PBA) and valproic acid (VPA) -two well-known HDACi -have shown an increase in SMN mRNA and protein levels in SMA fibroblasts. [15][16][17] Similar studies with hydroxyurea (HU) in EBV-immortalized SMA lymphoblasts 18 have shown an increase in the FL-SMN/D7-SMN (FL/D7 ratio). Pilot trials with these drugs have been performed in SMA patients and results were promising, [19][20][21] leading to the development of placebo-controlled clinical trials.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Recently, evidence has been provided that SMN2 gene expression can be enhanced by pharmacological treatment in vivo and/or in vitro, using different compounds. [9][10][11][12][13][14][15][16][17] The clinical efficacy of some of these compounds has been tested also in clinical trials. [18][19][20][21] The advances in SMA clinical research highlight the need of reliable biomarkers to monitor the efficacy at the molecular level of treatments during trials, the dosage of SMN transcripts or protein in peripheral blood samples being the only one potentially available.…”
Section: Introductionmentioning
confidence: 99%